Studi Kualitatif : Analisis Faktor-Faktor yang Mempengaruhi Pengobatan Pasien TB di Puskesmas Sentosa Baru - Veronika Bertua Simanjuntak; Erida Novriani; Razoki Razoki (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Tuberculosis (TB) is a global health problem, with Indonesia having the second highest number of cases in the world. Although morbidity and mortality rates from TB are still high, the disease is curable with proper treatment. The success of TB therapy can be influenced by various factors such as patient compliance, knowledge about TB, patient motivation, family support, education level, socioeconomic conditions, access to health facilities, the role of health workers, drug side effects, and comorbidities. This study aims to analyze the factors that influence the successful treatment of TB patients at Puskesmas Sentosa Baru. This study used a qualitative method with a cross-sectional descriptive approach, this study involved 15 TB patients who were interviewed in depth until the data reached the point of saturation, as well as observation and documentation. From the results of the research conducted, it was found that the factors that influence the success of patient treatment at Sentosa Baru Health Center are the level of patient compliance, level of knowledge, and patient motivation. Patients who have a better understanding of the disease tend to be more disciplined in undergoing therapy, while family support is a strong driver in improving patient adherence to treatment. Therefore, increased education, monitoring of adherence, and more intensive social support are needed so that patients can complete treatment optimally and break the chain of TB transmission.